Preservation of green ecology based on sharia consumption and production - Muhamad takhim; Risti Lia Sari (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The aim of this study is to introduce the concept and implementation of Sharia Consumption and Production (ShCP), in addition to the existing concept of Sustainable Consumption and Production (SCP) which is one of the Sustainable Development Goals (SDGs). In empirical reality, the application of SCP in society is not optimal and there is still a negative effect of consumption and production that is wild and damaging to the environment. This results in many losses both in terms of health, environmental imbalances and others. ShCP actualizes consumer awareness to fullfill consumption and production in accordance with what is needed and guarantees fulfillment of their needs by not endangering the environment, maintaining balance and justice in managing natural resources optimally, not wasteful, not excessive and not damaging the environment. This research method uses a literature review approach sourced from credible journals, books and authoritative news, making 6 maqoshid sharia as the ShCP target in achieving the blessing and blessing of Allah SWT. The results of this study indicate the Indicator of blessing and seeking God's blessing with consumption and production activities carried out with the priority scale of human needs; Primary (dharuriyyat), Secondary (hajiyat) and tertiary (tahsiniyat) safeguarding religion, soul, mind, descent, wealth and environment, (maqashid al-syari'ah) able to create a sustainable environment (green ecology) and strengthen SCP which is one of SDGs